'The Good Actions': A kindergarten children intervention to promote social and inclusive relationships. Issue 6 (1st November 2020) - Ginevra, Maria Cristina; Santilli, Sara; Di Maggio, Ilaria; Nota, Laura
ABSTRACT: A structured 10-sessions preventive training programme was implemented to improve kindergarten children's social skills. A total of 365 kindergarten children were involved, 187 of which were enrolled in the experimental group and 178 in the control group. Twenty-three (12 of the experimental group and 11 of the control group) kindergarten children with developmental disabilities who at pre-test presented low sociometric status and a low level of acceptance within their classes. The analyses found that at post-test the experimental group adopted and received more positive peer sociometric nominations, received less negative peer sociometric nominations, and provided more assertive answers than the control group. Moreover, kindergarten children with developmental disabilities that attended classes randomly assigned to the experimental group experienced less negative social behaviours and negative peer sociometric nominations and more positive sociometric nominations from their classmates. The study highlighted the potential of the intervention to promote positive peer relationships and friendships with others.